Monitoring perubahan massa area lumpur LAPINDO dengan metode gayaberat antar waktu: Stusi kasus Porong Jawa Timur - Indah Asmoro Wulan; Agus Setyawan (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
Sidoarjo mud occurs because of the emergence of hot mud and mudflow. Microgravity method used to monitor the mud, indicate that height change and know subsurface structure. Microgravity analysis based on microgravity data used to find out the value of microgravity changes. The result of microgravity value change indicate that the positive value is the addition of subsurface mass and land subsidence while the negative value is the reduction of subsurface mass. Three dimensional modeling based on gravity data were performed to find out the subsurface structure in the study area. The complete Bouguer anomaly is separated using an upward continuation to obtain regional and residual anomalies. 3D modeling were performed on complete Bouguer anomalies. 3D modeling results indicate of sedimentary rocks, sand, gravel, clay and indicate.Keywords: land subsidence, mudflow, microgravity method, 3D modelling